2022
DOI: 10.3389/fnut.2022.914715
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Oral Microbiome Associated With Diabetes, Overweight, and Dietary Components

Abstract: The Mediterranean diet (MedDiet) represents the traditional food consumption patterns of people living in countries bordering the Mediterranean Sea and is associated with a reduced incidence of obesity and type-2 diabetes mellitus (T2DM). The objective of this study was to examine differences in the composition of the oral microbiome in older adults with T2DM and/or high body mass index (BMI) and whether the microbiome was influenced by elements of a MedDiet. Using a nested case-control design individuals affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The results confirmed the impacts of DM on the dysbiosis of oral microbiota in diabetic rats and showed a significantly higher diversity of oral microbiota in samples of diabetic rats in contrast to that of rats in the CON group, in agreement with what several clinical studies had reported previously. 12,27 However, those results were contrary to the conclusion reported by Shaalan et al, 28 who found decreasing abundance and diversity of oral microbiota in subjects with T2DM. At the phylum level, it was found that the main species of oral bacterial colony of both diabetic rats and healthy ones were constituted by Firmicutes, Proteobacteria and Actinobacteria, which was similar to the findings of previous study.…”
mentioning
confidence: 57%
“…The results confirmed the impacts of DM on the dysbiosis of oral microbiota in diabetic rats and showed a significantly higher diversity of oral microbiota in samples of diabetic rats in contrast to that of rats in the CON group, in agreement with what several clinical studies had reported previously. 12,27 However, those results were contrary to the conclusion reported by Shaalan et al, 28 who found decreasing abundance and diversity of oral microbiota in subjects with T2DM. At the phylum level, it was found that the main species of oral bacterial colony of both diabetic rats and healthy ones were constituted by Firmicutes, Proteobacteria and Actinobacteria, which was similar to the findings of previous study.…”
mentioning
confidence: 57%
“…Gut microbiome diversity decrease emblematizes that pathogenic strains occupy the ecological niche of the intestinal mucosa, causing harmful bacterial metabolites or gut bacteria to enter the blood through the disrupted intestinal barrier and promote systematic chronic subacute in ammation [22,23]. This ongoing systemic in ammation can drive the progression of metabolic disease [24], cardiovascular disease [25],…”
Section: Discussionmentioning
confidence: 99%
“…In the diet, the intake of sugars and certain foods such as farmed animal meat, dairy products, refined vegetable oils, and processed grains affects the composition of the microbiota. Although the oral microbiota is not dependent on diet as an energy source ( 76 ), persistent sugar intake results in dysbiosis associated with a shift to glycolytic and acidophilic microbiota ( 77 ). Regarding smoking, the oral microbiota of smokers differs from that of nonsmokers in many respects, including reduced diversity, bacterial abundance, and metabolites.…”
Section: Oral Dysbiosismentioning
confidence: 99%
“…Diabetes and periodontal disease are mutually aggravating ( 107 ); oral microbiota dysbiosis induces insulin resistance by affecting the body’s immune inflammation and oxidative stress, adversely affecting diabetes ( 95 ). Conversely, elevated glucose levels in the saliva and tissues in patients with diabetes result in oral microbiota dysbiosis, with a shift to glycolytic and acidophilic microbiota ( 76 , 77 ). Patients with rheumatoid arthritis, systemic lupus erythematosus, and Sjögren’s syndrome also have reduced oral microbiota diversity; the individual candidate pathogens differ among studies ( 108 , 109 ).…”
Section: Association Between Oral Microbiota and Systemic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation